2010
DOI: 10.1111/j.1468-1293.2010.00866.x
|View full text |Cite
|
Sign up to set email alerts
|

Favourable evolution of virological and immunological profiles in treated and untreated patients in Italy in the period 1998-2008

Abstract: BackgroundThis study provides an estimate of the proportion of HIV-positive patients in Italian clinics showing an 'adverse prognosis' (defined as a CD4 count 200 cells/mL or an HIV RNA 450 HIV-1 RNA copies/mL) over time, and investigates whether this proportion varied according to patients' characteristics. MethodsWe estimated the annual proportion of patients with a CD4 count 200 cells/mL or HIV RNA 450 copies/mL out of the total number of patients in the Icona Foundation cohort seen in any given year, both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Regarding the other predictors of virological success, the positive impact of aging (possibly reflecting better adherence in older patients) is not new [23,24], as well as the positive impact of more recent calendar years, possibly reflecting a significant improvement in the drug regimens and in the overall standard of care [25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…Regarding the other predictors of virological success, the positive impact of aging (possibly reflecting better adherence in older patients) is not new [23,24], as well as the positive impact of more recent calendar years, possibly reflecting a significant improvement in the drug regimens and in the overall standard of care [25,26]. …”
Section: Discussionmentioning
confidence: 99%
“…Reports from the ICONA cohort showed that there was a significant increase in ART success rates in Italy between 1998 and 2008 [33]. Patients with CD4 T-cell counts ≤ 200/mm 3 decreased from 14 to 6% and the prevalence of HIV-RNA >50 copies/mL similarly decreased from 60% to 40% [33].…”
Section: Discussionmentioning
confidence: 99%
“…Reports from the ICONA cohort showed that there was a significant increase in ART success rates in Italy between 1998 and 2008 [33]. Patients with CD4 T-cell counts ≤ 200/mm 3 decreased from 14 to 6% and the prevalence of HIV-RNA >50 copies/mL similarly decreased from 60% to 40% [33]. The HIV Swiss cohort study reported 1-year incremental improvements in outcomes between the 2000 -2001 and 2004-2005 time intervals, both for patients with plasma HIV RNA <50 copies/mL and for CD4 T-cell count gains at 1 year of treatment [19].…”
Section: Discussionmentioning
confidence: 99%